Penyalahgunaan Narkotika oleh Anak Dengan Menerapkan Restorative Justice - Yudha, Moch Rahmania; Yulianis, M. Sifa' F. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In consideration of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, it is also stated that children are considered a gift from God Almighty who have value and dignity as complete human beings. In this research, the formulation of the problem is how to implement criminal law related to narcotics abuse by children, and what rights must be maintained in the context of narcotics abuse using a Restorative Justice approach. The aim of the research is to understand and evaluate how criminal law is applied in cases of narcotics abuse by children and analyze the special rights that children have in this situation using a Restorative Justice approach. The research method used is normative/qualitative research which focuses on the analysis of legal regulations and applicable legal texts. The conclusion of this research emphasizes that children are valuable assets for the state and their rights must be protected and immoral behavior must be avoided. Therefore, cooperation between the family, social environment, educational institutions and law enforcement officials is needed to protect children from narcotics abuse.